2018
DOI: 10.3389/fmicb.2018.00623
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Insights Into the Microbial Community and Nutrient Cycling in the Western Subarctic Pacific Ocean

Abstract: The composition and metabolic functions of prokaryotic communities in the western subarctic Pacific (WSP), where strong mixing of waters from the Sea of Okhotsk and the East Kamchatka Current result in transfer to the Oyashio Current, were investigated using a shotgun metagenome sequencing approach. Functional metabolic genes related to nutrient cycling of nitrogen, sulfur, carbohydrates, iron and amino acids were differently distributed between the surface and deep waters of the WSP. Genes related to nitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 74 publications
8
46
1
Order By: Relevance
“…However, the increases in denitrification genes in the greenhouse nursery could not be related to dynamics in the above taxa. It might be related to the increase with plant age in the relative abundance of Pseudomonas and Sphingomonas, as these bacterial genera contain members with denitrification characteristics (Deng et al, 2014;Hester et al, 2018;Li et al, 2018). It has been reported before that the C:N ratio influences denitrification process, as the abundance of denitrifiers positively responds to increased C availability in the soil environment (Miller et al, 2008(Miller et al, , 2009Henderson et al, 2010).…”
Section: Bacterial N-cycling Potential Is Dynamic Across Plant Agementioning
confidence: 96%
See 1 more Smart Citation
“…However, the increases in denitrification genes in the greenhouse nursery could not be related to dynamics in the above taxa. It might be related to the increase with plant age in the relative abundance of Pseudomonas and Sphingomonas, as these bacterial genera contain members with denitrification characteristics (Deng et al, 2014;Hester et al, 2018;Li et al, 2018). It has been reported before that the C:N ratio influences denitrification process, as the abundance of denitrifiers positively responds to increased C availability in the soil environment (Miller et al, 2008(Miller et al, , 2009Henderson et al, 2010).…”
Section: Bacterial N-cycling Potential Is Dynamic Across Plant Agementioning
confidence: 96%
“…These studies have revealed the importance of soil characteristics, management, and plant developmental stage on the assembly of the rhizosphere microbiome. Fewer studies have addressed the rhizosphere microbiota in perennial plants, where each growing season represents a small part of the plant's lifetime, and in particular, the bacterial communities are understudied (Wagner et al, 2016;Haas et al, 2018;Li et al, 2018). Perennial tree crops, including several conifers, are a source of products of economic importance, for example, wood, paper, and Christmas trees.…”
Section: Introductionmentioning
confidence: 99%
“…According to the barcode, the sequencing data were assigned to nine experimental groups (Control, N-limitation and P-limitation). The quality control of sequenced reads was performed as described in previous reports (Gong et al 2018, Li et al 2018. In addition, the reads that belong to different parts of the holobiont (i.e., D. magna and its gut microbiota) were separated by applying a previously reported method (Meng et al 2018).…”
Section: Disentangling Partner Reads From the Holobiont Systemmentioning
confidence: 99%
“…Chimeras were identi ed and removed using UCHIME (Edgar et al 2011). The remaining high-quality sequences were merged according to the experimental treatments, and the taxonomically assignment was processed with Silva database (version 123) by following the previous reported method (Li et al 2018). Finally, sequences were clustered into OTUs with a 97% sequence similarity cutoff.…”
Section: Analysis Of 16s Rrna Genementioning
confidence: 99%
“…According to the barcode, the sequencing data were assigned to nine experimental groups (Normal, Nlimitation and P-limitation). The quality control of sequenced reads was performed as described in previous reports (Gong et al 2018, Li et al 2018. In addition, the reads that belong to different parts of the holobiont (i.e., D. magna and its gut microbiota), were separated by applying a previously reported method (Meng et al 2018).…”
Section: Disentangling Partner Reads From the Holobiont Systemmentioning
confidence: 99%